THE IMPACT OF SOCIAL MEDIA PROMOTION ON PURCHASE DECISIONS IN SUKUN CHIPS SMEs IN KEDIRI - Syahputra, Erwin; Sumelvia Dewi, Anita; Hardiningrum, Iing Sri; Nadhiroh, Umi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Breadfruit chips or also known as ‘kripik sukun’ are a snack made from thinly sliced breadfruit, which is a starchy tropical fruit. They are typically fried or baked until crispy and seasoned with salt or other spices. Popular in many tropical regions, breadfruit chips offer a unique, crunchy alternative to traditional potato chips. The research focuses on the impact of social media promotions (WhatsApp, Instagram, TikTok) on purchasing decisions in marketing management. The objective is to analyze this impact both partially and simultaneously. The study used a quantitative approach with a sample of 94 respondents who shopped at breadfruit chips SMEs in Kediri through 3 social media platforms. Data collection was done through questionnaires and analysis techniques such as validity, reliability, classical assumption tests, multiple linear regression tests, and hypothesis testing. The sampling technique used was accidental sampling. The research results showed a regression equation of Y = 2.519 + 0.247X1 + 0.463X2 + 0.273X3 + e. The research hypothesis confirmed that WhatsApp, Instagram, and TikTok all have a significant effect on purchasing decisions at breadfruit chip SMEs in Kediri. The findings of this research provide valuable insights for marketing managers in SMEs, helping them understand the importance of utilizing social media platforms effectively to influence consumer behavior and drive sales.